PENYELESAIAN SENGKETA TANAH AYAHAN DESA DI DESA ADAT UMANYAR KABUPATEN KARANGASEM - I Nyoman Ngurah Alit (Kerta Dyatmika, 2021)
Abstract Given the importance of the function of land for the Balinese people, it is not uncommon for the use of customary land to cause various problems that lead to customary land disputes. It is very important to identify the legal position in the settlement of customary village father land disputes along with the authority for resolving customary village father land disputes that occurred in Karangasem Regency, so that based on this background the author finds the problem formulation, namely What are the forms of disputes that occur related to village father land in the village Umanyar custom of Karangasem Regency? How is the dispute resolution process related to the village father land that occurred in the Umanyar Traditional Village, Karangasem Regency?.The research method used in this study is an empirical legal research method. empirical legal research where field research is the main thing in activities or processes to find the rule of law, legal principles and legal opinions in order to answer the legal problems faced which of course focus on the behavior of the legal community (law in action).The form of land disputes in the Umanyar Traditional Village, Karangasem Regency, namely the Dispute on Ownership of the Land of Ayahan Desa where usually the disputing parties feel that the land that is the object of the dispute is their land, which is not uncommon for parties to recognize land ownership rights without the land certificate. For example, the Plaba Pura land dispute and the Use Rights Dispute on Ayahan Desa Land. Usually the parties to the dispute feel that the other party has controlled and worked on the land belonging to another person which is the object of the dispute without a legal basis for rights and legal basis, for example plantation land disputes. The process of resolving land disputes based on Awig-Awig in the Umanyar Traditional Village, Karangasem Regency is based on Pawos 23 paragraph (5) awig-awig in the Umanyar traditional village where it is not allowed to sell or ratify village ownership if it is not approved by the village community so that in the event of a dispute it is necessary to village deliberation efforts are carried out with village officials as mediators in mediation efforts to resolve disputes, but if the disputing parties do not find a dispute resolution in the village deliberation, dispute resolution can also be resolved through legal channels if the disputing parties are not satisfied with the results of the mediation decision. customary village and if the disputing parties want it.